Orthotopic hepatic cancer: radiofrequency hyperthermia-enhanced intratumoral herpes simplex virus-thymidine kinase gene therapy - Xiong, Fu (Oncotarget, 2017)
PURPOSE: To validate the feasibility of using interventional radiofrequency hyperthermia(RFH) to enhance herpes simplex virus-thymidine kinase (HSV-TK)/ganciclovir (GCV) gene therapy of rat orthotopic hepatic cancer. MATERIAL AND METHODS: Rat hepatocellular carcinoma cells (MCA-RH-7777) were transduced with lentivirus/luciferase gene for optical imaging. In-vitro experiments with the luciferase cells and in-vivo experiments on rats with orthotopic hepatic tumors were divided into four treatment groups: (i) HSV-TK/GCV-mediated gene therapy combined with RFH; (ii) gene therapy alone; (iii) RFH alone; and (iv) phosphate buffered saline (PBS). Cell viability was evaluated by MTS assay and confocal microscopy, and HSV-TK gene expression in cells and tumors was quantified by western blotting. Bioluminescent optical imaging and ultrasound imaging were used to monitor and compare the photon signal and tumor size changes among different treatment groups overtime, respectively. The imaging findings were correlated with histology. RESULTS: For in-vitro experiments, the combination therapy group (gene therapy + RFH) demonstrated the lowest cell proliferation by MTS assay, compared to the gene therapy alone, RFH alone, and PBS (26.1±3.2% vs 50.4±4.6% vs 82.9±6.3% vs 100%, p<0.01). The combination therapy group also showed fewer survived cells by the confocal microscopy and the lowest bioluminescent signal by the optical imaging. For in-vivo experiments, the combination therapy group demonstrated a significantly decreased signal intensity on the bioluminescent optical imaging (0.57±0.09, 1.06±0.10 vs 3.43±0.27 vs 3.85±0.12, p<0.05) and smallest tumor volume by ultrasound imaging (0.28±0.11 vs 1.28±0.23vs 4.64±0.35 vs 6.37±0.36, p<0.05), compared to the other three groups. Additionally, these imaging findings correlated well with the histological confirmation. CONCLUSION: It is feasible to use RFH to enhance HSV-TK/GCV gene therapy of hepatic tumors in in-vitro and in-vivo settings, as assessed by molecular imaging. This technical development may provide a novel opportunity for effective treatment of liver malignancies by employing simultaneous integration of radiofrequency technology, interventional oncology, and direct intratumoral gene therapy.